MEASURES TO PROTECT LEAF LETTUCE FROM HARMFUL ORGANISMS IN GREENHOUSE CONDITIONS - Kosylovych , Г.; Holiachuk , Ю.; Lenchuk , С. (Bulletin of Lviv National Environmental University. Series Agronomy, 2024)
It is crucial to take measures to safeguard plants from harmful organisms to preserve harvests and maintain the high quality of lettuce products. When growing Lollo Rossa and Lollo Bionda leaf lettuce in greenhouses, it is important to avoid using chemical plant protection agents and instead focus on preventive measures and the use of biopesticides. When growing Lollo Rossa and Lollo Bionda leaf lettuce in greenhouses, it is recommended to use the biofungicide Trichodermin (VIRIDIN) at a rate of 20 g per 5 liters of water to protect the plants from damage caused by pathogens. Additionally, the bioinsecticide Actoverm should be applied at a rate of 50 ml per 5 liters of water to protect the plants from pests. The use of the microbiological preparation Trichodermin (VIRIDIN) on leaf lettuce of Lollo Rossa and Lollo Bionda in greenhouse conditions ensured high effectiveness of fungicidal action against downy mildew and gray rot, biological preparations Actoverm, Bitoxybacillin BTU – a high insect-acaricidal effect against aphids, whiteflies and spider mites. The number of leaves formed by lettuce plants and the diameter of the bush plant increased, respectively on 3 pcs and on 9.4–10.9 cm when the biofungicide Trichodermin (VIRIDIN) was applied against phytopathogens and the bioinsecticide Actoverm against pests. The indicator of the greater fresh mass of one lettuce plant of Lollo Rossa and Lollo Bionda in the experimental variants ensured a higher yield, of 1.2 kg/m2 and 1.4 kg/m2 respectively. With the use of the biofungicide Trichodermin (VIRIDIN) at the rate of 20 g per 5 l of water against phytopathogens and the bioinsecticide Actoverm at the rate of 50 ml per 5 l of water against pests, the yield of Lollo Bionda lettuce was the highest, which amounted to 1.4 kg/m2 of additional yield compared to the control, the yield of Lollo Rossa lettuce was 1.2 kg/m2 higher than that of the control.